Prospects for a personalized peptide vaccine against lung cancer - Yoshiro Nakahara; Taku Kouro; Yuka Igarashi; Mamoru Kawahara; Tetsuro Sasada (Taylor & Francis Group, 2019)
Introduction: The tumor characteristics and immunological status of the host should be carefully considered for the successful development of cancer peptide vaccines. Recently, personalized peptide vaccines (PPV) that individually select antigens for each patient are being developed for lung cancer. Areas covered: Novel PPV, in which appropriate vaccine antigens are selected in each patient by assessing preexisting immunity to a panel of vaccine peptide candidates, have been attempted with promising results in early-phase clinical trials for lung cancer. Additionally, PPV targeting neo-antigens derived from genetic mutations have been currently attempted with high anticipation of success in various cancers, because they can be recognized as foreign by the host immune system. In this review, we present an overview of the current progress and future directions of such PPV for patients with lung cancer. Expert opinion: Both genetic characterization of tumor cells and assessment of the immune responses to potential tumor antigens might be a key component for facilitating successful cancer vaccine development. In addition, not only selection of immunogenic epitopes, but also appropriate modulation of the host immunological status should be considered; clinical trials combining neo-antigen vaccines and anti-PD-1 antibodies for lung cancer are currently ongoing and their results are awaited.